1994
DOI: 10.1051/mmm:0199400504-6029100
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Si(111) surfaces etched in 40% NH4F: Influence of the doping

Abstract: Abstract. 2014 The morphology of precisely oriented n and p+ type Si(111) hydrogenated surfaces has been studied by UHV-STM and AFM at ambient after "chemical" etching in 40% NH4F. Whereas atomically flat surfaces are obtained with the n-type samples, the surface of p+ substrates is rough. It is shown that these observations stem from a variation of the partition between the chemical (anisotropic) and the electrochemical (isotropic) components of the etching reaction. This is the uptake of the latter reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We note, however, that the broader Si 2p and C 1s peaks observed for the HDp Si adsorbed monolayers (Figure a and c, respectively) are a result of the unusual structural and chemical properties of the freshly etched HDp Si surface. It has been shown that such surfaces are much rougher, compared to the n-Si surface, and that they are not always H-terminated. As a result, this Si–C interface is not as well ordered or defined as that for other Si doping levels. For further characterization of the HDp samples, see the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…We note, however, that the broader Si 2p and C 1s peaks observed for the HDp Si adsorbed monolayers (Figure a and c, respectively) are a result of the unusual structural and chemical properties of the freshly etched HDp Si surface. It has been shown that such surfaces are much rougher, compared to the n-Si surface, and that they are not always H-terminated. As a result, this Si–C interface is not as well ordered or defined as that for other Si doping levels. For further characterization of the HDp samples, see the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, medium-doped samples had to be used for the IR studies. 39,42,43 The current-voltage (I-V) isotherms, I-V-T curves, for a Si-(CH 2 ) 17 CH 3 (C18) monolayer/Hg junction are shown in Fig. 2a.…”
Section: Resultsmentioning
confidence: 99%
“…The immersion times and temperatures are (b) 480 min, 5 °C, (c) 240 min, 63 °C, and (d) 60 min, 81 °C. White lines forming a triangle, added to (b), indicate the 〈1̄1̄2〉 direction and equivalents of the Si(111) surface, determined from the directions of trigonal etch pits whose edges are known to be in parallel to the 〈1̄1̄2〉 direction or equivalents. , …”
Section: Resultsmentioning
confidence: 99%